Pelatihan Pemanfaatan Media Audio Visual dalam Pembelajaran Menyimak Cerita bagi Siswa Sekolah Dasar di Purwakarta - Neneng Sri Wulan; Wina Mustikaati; Ela Azizah; Dian Aidilafitri; Febrina Nur Giyantika; Jubaedah Fitri Anjani; Muhammad Agni Imanulloh; Silvania Nur Jannatin Aliyah; Indra Nugrahayu Taufik; Yupi Yuliawati (Universitas Pendidikan Indonesia Kampus Purwakarta, 2022)
This study is motivated by the problems faced by elementary school students in listening comprehension. Audio-visual media is an alternative solution in listening activities in the class, such as animated films and videos. This training activity aims to develop the ability to listen to stories of elementary school students through audio-visual media. The activity implementation method includes three stages: the preparation stage, the activity implementation stage, and the evaluation stage. This training activity subject is 20 students of grade 3 at SDN Nagri Tengah Purwakarta. The results of the implementation of this activity indicate that with the application of audio-visual media, students understand the story's content more quickly, are active and are motivated to participate in story-listening learning activities. As many as 60% or 12 students get good marks above the KKM. This result shows that audio-visual media positively impacts students' ability to listen to stories.